The feasibility, time savings and economic impact of a designated time appointment system at a busy HIV care clinic in Kenya: a randomized controlled trial. Issue 1 (9th July 2015) - Kwena, Zachary A; Njoroge, Betty W; Cohen, Craig R; Oyaro, Patrick; Shikari, Rosemary; Kibaara, Charles K; Bukusi, Elizabeth A
Abstract : Introduction: As efforts are made to reach universal access to ART in Kenya, the problem of congestion at HIV care clinics is likely to worsen. We evaluated the feasibility and the economic benefits of a designated time appointment system as a solution to decongest HIV care clinics. Methods: This was an explanatory two‐arm open‐label randomized controlled trial that enrolled 354 consenting participants during their normal clinic days and followed‐up at subsequent clinic appointments for up to nine months. Intervention arm participants were given specific dates and times to arrive at the clinic for their next appointment while those in the control arm were only given the date and had the discretion to decide on the time to arrive as is the standard practice. At follow‐up visits, we recorded arrival and departure times and asked the monetary value of work participants engaged in before and after clinic. We conducted multiple imputation to replace missing data in our primary outcome variables to allow for intention‐to‐treat analysis; and analyzed the data using Mann–Whitney U test. Results: Overall, 72.1% of the intervention participants arrived on time, 13.3% arrived ahead of time and 14.6% arrived past scheduled time. Intervention arm participants spent a median of 65 [interquartile range (IQR), 52–87] minutes at the clinic compared to 197 (IQR, 173–225) minutes for control participants ( p <0.01). Furthermore, intervention arm participants were more productively engaged on their clinic days valuing their cumulative work at a median of USD 10.5 (IQR, 60.0–16.8) compared to participants enrolled in the control arm who valued their work at USD 8.3 (IQR, 5.5–12.9; p =0.02). Conclusions: A designated time appointment system is feasible and provides substantial time savings associated with greater economic productivity for HIV patients attending a busy HIV care clinic.